Growth and Welfare under Endogenous Lifetime - Maik T. Schneider; Ralph Winkler (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the role of endogenous healthcare choices by households to extend their expected lifetimes on economic growth and welfare in a decentralized overlapping generations economy with the realistic feature that households' savings are held in annuities. We characterize healthcare spending in the decentralized market equilibrium and its effects on economic growth. We identify the moral-hazard effect in healthcare investments when annuity rates are conditioned on average mortality and explain the conditions under which this leads to over-investment in healthcare. Moreover, we specify the general equilibrium effects and macroeconomic repercussions associated with this moral-hazard effect. In a numerical simulation of our model with OECD data, we find that the moral-hazard effect may be substantial and implies sizeable welfare losses of approximately 1.5%. At a more general level, our study suggests that welfare improvements from longevity increases may be lower than suggested when considered in planner economies.
Keywords: O40; I10; J10; 330; annuities; economic growth; endogenous longevity; healthcare expenditures; healthcare technology; moral hazard; pension systems; welfare analysis